Adaptive Management in the Courts - Fischman, Robert L.; Ruhl, J.B. (Minnesota Law Review, 2010)
Adaptive management has become the tonic of natural resources policy. With its core idea of “learning while doing,” adaptive management has infused the natural resources policy world to the point of ubiquity, s urfacing in everything from mundane agency permits to grand presidenti al proclamations. Indeed, it is no exaggeration to suggest that these days adaptive management is natural resources policy. But is it workin g? Does appending “adaptive” in front of “management” somehow make nat ural resources policy, which has always been about balancing competing claims to nature’s bounty, something more and better? Many legal and policy scholars have asked that question, with mixed reviews. Their ev aluations, however, have rested on theory, program-specific surveys, a nd isolated case studies. This article provides the first comprehensiv e review of adaptive management from the perspective that likely matte rs most to the natural resource agencies practicing adaptive managemen t - how is it faring in the courts? Part I of the Article examines the theory, policy, and practice of adaptive management, focusing on the experience of the federal resource management agencies. The end produc t in practice is something we call “a m-lite,” a watered down version of the theory that resembles ad hoc contingency planning more than it does planned “learning while doing.” This gap between theory and pract ice leads to profound disparities between how agencies justify decisio ns and how adaptive management in practice arrives at the courthouse d oorsteps. In Part II we review how these disparities have played out i n courts considering claims that agency practice of adaptive managemen t has not lived up to its theoretical promise or to the legal demands of substantive and procedural environmental law. We extract three key themes from the body of case law in this respect. Part III extends fro m the existing case law to draw lessons for agencies and Congress abou t the future practice of adaptive management. Our ultimate message to agencies is that a m-lite can be an effective decision method - and on e that survives judicial scrutiny - but agencies must be more discipli ned about its design and implementation. This includes resisting the t emptation to employ adaptive management to dodge burdensome procedural requirements, substantive management criteria, and contentious stakeh older participation. If faithfully followed and enforced, this model, despite its flaws, could serve as an important component of natural re sources policy to confront problems of the future as daunting as clima te change.